2010
DOI: 10.3928/01477447-20101021-13
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Arthroplasty in Younger Patients: A 13-Year Follow-Up Study

Abstract: Total knee arthroplasty (TKA) is a well-established treatment at the end stage of a degenerated knee joint. This operative treatment generally relieves pain, improves physical function, and has a high level of patient satisfaction, especially in the elderly. Younger patients, however, are demanding and have a higher level of physical activity compared to elderly patients. One could therefore expect more mechanical problems such as prosthetic loosening and polyethylene wear after long-term follow-up. The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 20 publications
1
18
1
1
Order By: Relevance
“…Odland et al10) stated that there would be difference in the outcomes of TKA between rheumatoid arthritis patients and degenerative arthritis patients. On the other hand, Bisschop et al1) reported that the survival rates and function scores were not significantly different between the rheumatoid arthritis patients and degenerative arthritis patients in ≤60 years of age cohorts. In our study, the TKA failure rate was 7% in the ≤55 years of age group and 2% in the >55 years of age group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Odland et al10) stated that there would be difference in the outcomes of TKA between rheumatoid arthritis patients and degenerative arthritis patients. On the other hand, Bisschop et al1) reported that the survival rates and function scores were not significantly different between the rheumatoid arthritis patients and degenerative arthritis patients in ≤60 years of age cohorts. In our study, the TKA failure rate was 7% in the ≤55 years of age group and 2% in the >55 years of age group.…”
Section: Discussionmentioning
confidence: 96%
“…It has demonstrated excellent clinical efficacy in terms of postoperative pain, physical function, and patient satisfaction and contributed to long-term implant survival and patient's quality of life1,2). The procedure has been performed commonly on elderly patients and rarely on young patients with knee joint disorders accompanied by severe pain, such as rheumatoid arthritis3,4).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the unique set of pressures faced by younger people (including work responsibilities and parenting roles), there has been little research into the well-being of those with hip or knee OA. As most research involving younger people with OA has focused on the outcomes of surgery to repair or replace damaged joints,7 8 the quality of life and health status experienced by younger people remain poorly understood. This would form an important baseline in order to understand the impact of any intervention.…”
Section: Introductionmentioning
confidence: 99%
“…3 7 Bei der 55-jäh-rigen Rheumatikerin bestand bei Erstvorstellung eine massive Destruktion des medialen Tibiaplateaus mit höchstgradiger Instabilität des Kniegelenks (a); Versorgung mit teilgekoppelter Knieprothese (b) tation eine verbesserte Ausrichtung der femoralen [13] und tibialen Komponente [12] sowie eine geringere Abweichung bei der Rekonstruktion der mechanischen Beinachse [13] beschrieben. Demgegenüber werden als Nachteil längere Operationszeiten sowie Frakturen im Bereich der eingebrachten Markierungsnägel [2] beschrieben.…”
Section: Navigiert Oder Nichtnavigiert?unclassified